(untitled) (Iraqi Journal of Civil Engineering, 2012)
This paper presents a new and improved design procedure in shear for reinforced concrete normal members without shear reinforcement (stirrups) using the techniques of dimensional analysis and multiple regression analysis. A total of 334 data sets have been obtained from existing sources of reinforced concrete shear test results covering a wide range of beam properties and test methods. The proposed equation is applied to existing test data for these reinforced concrete normal beams (shear span to depth ratio (a/d) greater than or equals to 2.0) and the results are compared with those predicated by ACI and BS codes. It can be also noted that the test results are in better agreement with the proposed cracking shear strength equation because of the excellent correlation between experimental results and theoretical values.